Ferroptosis: mechanism and role in diabetes-related cardiovascular diseases - Ziyi Wang; Chao Wu; Dong Yin; Kefei Dou (Cardiovascular Diabetology)
Abstract Cardiovascular diseases represent the principal cause of death and comorbidity among people with diabetes. Ferroptosis, an iron-dependent non-apoptotic regulated cellular death characterized by lipid peroxidation, is involved in the pathogenesis of diabetic cardiovascular diseases. The susceptibility to ferroptosis in diabetic hearts is possibly related to myocardial iron accumulation, abnormal lipid metabolism and excess oxidative stress under hyperglycemia conditions. Accumulating evidence suggests ferroptosis can be the therapeutic target for diabetic cardiovascular diseases. This review summarizes ferroptosis-related mechanisms in the pathogenesis of diabetic cardiovascular diseases and novel therapeutic choices targeting ferroptosis-related pathways. Further study on ferroptosis-mediated cardiac injury can enhance our understanding of the pathophysiology of diabetic cardiovascular diseases and provide more potential therapeutic choices.